LOW BACK PAIN (LBP) PADA PETANI DI DESA RINGINSARI KANDAT KEDIRI - setyorini, dwi; Hayati, Farida; Septian Pradana, Dimas (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Low back pain (LBP) is a common complaint in farmers due to agricultural work such as bending, standing, squatting, lifting and carrying loads, and the back as the main support. These activities have a high level of tension and involve many repetitive movements causing the spinal muscles to be continuously overloaded resulting in low back pain. The aim of this study was to determine the level of low back pain in farmers in the Ringinsari Kandat Village farmer group, Kediri. This study used a descriptive design. The population in this study were 60 members of the farmer group with a purposive sampling technique, a sample of 18 respondents was obtained. Data collection used a questionnaire sheet, data analysis used a percentage. The results of the study showed that most of the respondents (55.6%) had low back pain on a scale of 5, with an average value of 4.44. Agricultural work has a high level of tension and involves many repetitive movements. This causes the spinal muscles to be overloaded due to work that is done continuously without time to relax, resulting in pain in the farmers' lower backs. Respondents are advised to minimize continuous static loads and pay attention to ergonomics at work to prevent and reduce the level of Low Back Pain.